Konsumsi Energi, Zat Gizi Makro, Aktivitas Fisik, dan Kadar Glukosa Darah Siswa SMP di Tangerang - Ayla Namira Handzolah; Vitria Melani; Hendra Wijaya; Dessy Aryanti Utami; Kurnia Dwi Juliani; Rachmanida Nuzrina; Nadiyah (Politeknik Negeri Jember, 2026)
Diabetes Mellitus (DM) is a non-communicable disease caused by insulin resistance. Factors that can cause DM include gender, age, family history of DM, race and ethnicity, history of low birth weight, overweight, lack of physical activity, hypertension, dyslipidemia, consumed foods, and foods high in glucose. Therefore, lifestyle changes are necessary by modifying eating habits and physical activity to prevent the risk of diabetes mellitus. This study aims to identify the relationship between energy intake, macronutrients, physical activity, and random blood glucose levels in junior high school students at SMP Budi Mulia. This quantitative study uses a cross-sectional method. The research was conducted at SMP Budi Mulia, Tangerang City, with a sample of 63 respondents selected through stratified random sampling. Primary data was obtained by filling out questionnaires on age, gender, and physical activity, followed by a 2x24 hour food recall interview, and measurement of random blood glucose levels. The study results using correlation tests showed a relationship between energy intake and blood glucose levels (pv = 0.0001; r = 0.520), protein intake and blood glucose levels (pv = 0.003; r = 0.363), fat intake and blood glucose levels (pv = 0.0001; r = 0.455), and carbohydrate intake and blood glucose levels (pv = 0.0001; r = 0.464).Keywords: blood glucose, macronutrients, physical activity